Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Induvidualization (TAI) Terhadap Hasil Belajar Matematika Siswa Kelas VII UPTD SMP Negeri 12 Pematangsiantar (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to find out how the influence of the Team Assisted Individualization (TAI) type cooperative learning model on students' mathematics learning outcomes in class VII algebra form material at UPTD SMP Negeri12 Pematang Siantar. The approach taken in this study is a quantitative approach. The instruments used in this study were questionnaires (questionnaires) and learning outcome tests. Data analysis techniques use prerequisite tests, namely normality tests and linearity tests. To test whether Team Assisted Individualization (TAI) type cooperative learning models affect learning outcomes, a simple linear regression test was used. From the simple linear regression test performed, the regression equation Y = 8.804 + 0175.X which can be interpreted as every addition of 1% of the questionnaire value will cause an increase in learning outcome test scores of 0.175. It can be seen that the value of the regression coefficient is greater than 0 (positive value), so there is a positive influence between variable 50,8%.